Pre-breeding canola for heat stress tolerance – a prototype facility for large-scale screening at flowering stage - Chen, S.; Stefanova, Katia; Siddique, K.; Cowling, W. (2021)
This research is developing methodology to facilitate large-scale screening of heat stress tolerance in canola at flowering stage, and will identify heat tolerant germplasm for Australian plant breeders. The new methods and heat tolerant germplasm will be transferred to canola breeders, which will accelerate the future commercial release of heat tolerant varieties. Our aim is to help Australian growers to maintain canola productivity as temperatures rise in response to climate change.